Early gene expression changes in spinal cord from SOD1G93A Amyotrophic Lateral Sclerosis animal model - Oliveira, Gabriela P.; Alves, Chrystian J.; Chadi, Gerson (Frontiers in Cellular Neuroscience, 2013)
Amyotrophic Lateral Sclerosis (ALS) is an adult-onset and fast progression neurodegenerative disease that leads to the loss of motor neurons. Mechanisms of selective motor neuron loss in ALS are unknown. The early events occurring in the spinal cord that may contribute to motor neuron death are not described, neither astrocytes participation in the pre-symptomatic phases of the disease. In order to identify ALS early events, we performed a microarray analysis employing a whole mouse genome platform to evaluate the gene expression pattern of lumbar spinal cords of transgenic SOD1G93A mice and their littermate controls at pre-symptomatic ages of 40 and 80 days. Differentially expressed genes were identified by means of the Bioconductor packages Agi4x44Preprocess and limma. FunNet web based tool was used for analysis of over-represented pathways. Furthermore, immunolabeled astrocytes from 40 and 80 days old mice were submitted to laser microdissection and RNA was extracted for evaluation of a selected gene by qPCR. Statistical analysis has pointed to 492 differentially expressed genes (155 up and 337 down regulated) in 40 days and 1105 (433 up and 672 down) in 80 days old ALS mice. KEGG analysis demonstrated the over-represented pathways tight junction, antigen processing and presentation, oxidative phosphorylation, endocytosis, chemokine signaling pathway, ubiquitin mediated proteolysis and glutamatergic synapse at both pre-symptomatic ages. Ube2i gene expression was evaluated in astrocytes from both transgenic ages, being up regulated in 40 and 80 days astrocytes enriched samples. Our data points to important early molecular events occurring in pre-symptomatic phases of ALS in mouse model. Early SUMOylation process linked to astrocytes might account to non autonomous cell toxicity in ALS. Further studies on the signaling pathways presented here may provide new insights to better understand the events triggering motor neuron death in this devastating disorder.